Overlap syndrome: a literature review of the coexistence of rheumatoid arthritis, ankylosing spondylitis and Sjögren’s syndrome - Macena, Bruno Balbino (2021)
Overlap Syndrome is a term used to describe the association of two or more independently diagnosed diseases in the same patient. In this article, the authors develop a literature review of the main studies published about the coexistence of ankylosing spondylitis with rheumatoid arthritis and Sjögren's syndrome. The aim of the study is to build an overview of the evidence available in the scientific literature on cases of patients with this triple association or other double associations, such as between rheumatoid arthritis and ankylosing spondylitis or between ankylosing spondylitis and Sjögren's syndrome. Sixteen scientific articles were selected among a hundred and twenty-six articles initially chosen in the main national and international scientific databases. The results show that the clinical, radiological and serological characteristics of each disease can be partially or completely present. The present review shows us the importance of studying unusual associations due to the lack of relevant information in the literature and at the same time indicates that early therapeutic intervention is essential to improve the quality of life of patients.